Identification of possible factors influencing development temporomandibular joint disorders of patients according to their anamnestic data - Макєєв, Валентин Федорович; Телішевська, Оксана Дмитрівна; Михайлевич, Марта Юріївна (Actual Dentistry, 2019)
Resume. The question of the etiology and pathogenesis of the TMD’s is not fully understood, so finding ways to treat this pathology is often difficult, because understanding the etiology of the temporomandibular disorders is extremely important in recognizing and eliminating potential pathological factors. The attention of dentists should be drawn to the need to carefully collect the anamnesis of a potential patient for the identification of diseases that may lead to TMD on the patient's initial examination. This can prevent them from developing or facilitating their development. The goal: identification of possible factors that influence the development of TMD’s patients according to their anamnestic data. Results. The study found that the most significant factors were: traumatic brain injury (TBI), frequent dental treatment, frequent sore throats, and the presence of herpes zoster. Among the associated comorbidities, it is advisable to single out such pathologies as scoliosis (its various forms) and cervical osteochondrosis. Other common somatic pathologies are hypermobility of all joints and allergies. Conclusions. Analysis of the anamnestic data of patients with temporomandibular joint disorders revealed the possibility of multifactorial etiological factors that may influence the development of temporomandibular joint disorders or create the background for their occurrence. Key words: temporomandibular disorders, anamnesis